The origins of the term “luri languageˮ: a historical investigation (Journal of Oriental Studies, 2021)
The present article deals with the controversial relationship of Luri Language with Persian, and aims to find out whether Luri is a distinct family from Persian even in the middle period, or it must be considered only a modern dialect of Middle Persian. Based on historical evidence and from a diachronic point of view, the authors put forward the theory that not only isnʼt there a single language as Luri but the so-called Luri varieties are in fact modern daughter languages of Middle Persian. This idea is largely based on the previous literature on Luri, but also supported by other findings presented in this article. The mutual intelligibility break among Luri varieties, the lack of reference to Lur tribe in the historical sources of the early Islamic centuries, the etymology of the word “Lurˮ, and the historical accounts of Luri language provide the main arguments and sources of evidence in support of the above theory which are complemented by a grammatical comparison between Luri and historical stages of Persian language. Key words: Luri Language, Early New Persian, Middle Persian, Dialectology, Historical Linguistics